'Yarn about it': Aboriginal Australian women's perceptions of the impact of routine enquiry for intimate partner violence. Issue 7 (3rd July 2019) - Spangaro, Jo; Herring, Sigrid; Koziol-McLain, Jane; Rutherford, Alison; Zwi, Anthony B.
Abstract: Aboriginal women globally are disproportionately affected by intimate partner violence (IPV) and face additional barriers to help-seeking. It is crucial that interventions for IPV are made safe for Indigenous women, given inflated rates of statutory intervention and widespread institutional racism. As part of a larger study of antenatal IPV screening, we interviewed 12 Aboriginal Australian women about the perceived impact of an antenatal IPV routine enquiry intervention. Seven women reported positive impact, and five women reported the absence of positive impact. Qualitative comparative analysis was used to map pathways to perceived impact. Cultural safety – the practice of countering tendencies in health care that undermine safety – was a key condition for positive impact. Others included: (i) continuity of care; (ii) asking about abuse without judgement and with care; and (iii) support and validation. Absence of these factors also typified pathways for nil positive impact. Naming the abuse, a sense of connection, unburdening, taking steps to safety and enabling informed care were all reported benefits. Two women reported explicitly negative impacts: one noted a sense of intrusion, and the other, disengagement from the health service. Interventions for IPV have the potential to benefit Indigenous women where cultural safety is prioritised.